Confucianism in China. - Smagulova., K. K. (Journal of Oriental Studies, 2016)
This article considers the versatile role of confucianism, socio- political situation, the freedom of confession and its place in policy, processes of integration. The place traditions and customs of Chinа folks in Chinese society are also described. In this way articleconsiders the processes of development features of religious identities and confessional relations in China.